Thiruvalluvar’s Observation On Nature: A Study On The Classical Tamil Text Thirukkural - Dr. M. Kalaiarasan (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2018)
Thiruvalluvar was the foremost thinker of nature among the prominent classical Tamil poets. He not only wrote about morality but also about various themes and subjects. He lived with the nature which portrayed in his works. His famous work Thirukkural is applicable for all the time and people. Most of the researches in Tamil shows how he is associated with nature and the present paper is an attempt to show about his keen observation on the nature.